(untitled) (World Conference on Social Sciences, Law and Public Policy, 2026)
The article examines the pedagogical potential of digital technologies for improving the effectiveness of mother-tongue teaching in higher education. It discusses how digital platforms, electronic corpora, multimedia resources, mobile applications and artificial intelligence systems can contribute to students’ linguistic, communicative and textual competence. The study argues that digitalization should not be reduced to the technical modernization of traditional lessons, because it also transforms educational content, teaching methods and patterns of interaction. Particular attention is given to the design of digital assignments, personalized learning trajectories and immediate formative feedback. Challenges related to unequal access, academic integrity, teachers’ digital competence and the limited availability of high-quality national-language resources are also considered. The article proposes a pedagogically grounded model for integrating digital technologies into university mother-tongue courses.